2020
DOI: 10.47811/bhj.96
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Occupational noise induced hearing loss (ONIHL) among industrial workers in Bhutan.

Abstract: Introduction: Exposure to any type of noise has a potential risk. Higher the level of noise and longer duration of exposure, the more the risk for the hearing sensitivity and health as a whole. The objective of the study is to determine the prevalence of Occupational Noise Induced Hearing Loss (ONIHL) among the industrial workers in Bhutan and to ascertain high risk establishment and vulnerable occupations. Methods: The hearing assessment was conducted among 1638 workers considering different types of industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…14 The present study showed the mean age of the steel weaving factory workers was 31.10 years within the age group of 25-55 years as shown in Table1. The result was found to be consistent with the studies that Bhutan, Thailand belong to the age group of 31-40 years [17][18][19]. The workers of the steel weaving factorywork in 8 hours shift duration.…”
supporting
confidence: 91%
“…14 The present study showed the mean age of the steel weaving factory workers was 31.10 years within the age group of 25-55 years as shown in Table1. The result was found to be consistent with the studies that Bhutan, Thailand belong to the age group of 31-40 years [17][18][19]. The workers of the steel weaving factorywork in 8 hours shift duration.…”
supporting
confidence: 91%
“…The prevalence, 41.6% of hearing loss in this study, it's found that more than half (50.7%) of the industrial workers are suffering from hearing impairment either due to ONIHL or other types of hearing impairments. Which was higher than 34% found the studies conducted in Ethiopia, 30.86% in Turkey, 38% found in India, 33.46% in Bangladesh, 30% in Jordan, 35% in Canada and 27.9% in Bhutan 13,16,17,19,[21][22][23] . These differences of hearing loss may have resulted from the use of hearing loss prevention programs for all workers whose unprotected 8-hr TWA exposures equal or exceed 85 dB(A) with assessment of noise exposure and audiometric monitoring.…”
Section: Resultsmentioning
confidence: 81%
“…The prevalence, 41.6% of hearing loss in this study, it's found that more than half (50.7%) of the industrial workers are suffering from hearing impairment either due to ONIHL or other types of hearing impairments. Which was higher than 34% found the studies conducted in Ethiopia, 30.86% in Turkey, 38% found in India, 33.46% in Bangladesh, 30% in Jordan, 35% in Canada and 27.9% in Bhutan 13,16,17,19,[21][22][23] . These differences of hearing loss may have resulted from the use of hearing loss prevention programs for all workers whose unprotected 8-hr TWA exposures equal or exceed 85 dB(A) with assessment of noise exposure and audiometric monitoring.…”
Section: Resultsmentioning
confidence: 81%